The impact of perceived organizational support and human resources practices on innovative work behavior: does gender matter? - Al-Taie, Moyassar; Khattak, Mohammad Nisar (Frontiers in Psychology, 2024)
Modern organizations nowadays are striving to survive and thrive within the intense competition, complex environment, and ongoing globalization. Employees' innovative work behavior has become the primary vehicle for these organizations to achieve this aim. The purpose of this study is to examine the effect of perceived organizational support (POS) and high commitment human resource practices (HCHRPs) on employee innovative work behaviors (IWB) within the moderating role of gender. Data was obtained from 359 academic staff members working in 124 higher education institutions in all emirates of the United Arab Emirates (UAE). Findings revealed that POS and HCHRPs are positively related to employee innovative work behaviors. Moreover, the moderating effect of gender on the direct relationship between POS and employee innovative work behaviors was significant, but not significant on the direct relationship between HRPs and employee innovative work behaviors.Implications of the findings for academics and practitioners were presented, and limitations and future research were discussed.